1994
DOI: 10.1111/j.1365-2621.1994.tb06967.x
|View full text |Cite
|
Sign up to set email alerts
|

Provitamin A and Ascorbic Acid Content of Fresh Pepper Cultivars (Capsicum annuum) and Processed Jalapeños

Abstract: Alpha and beta carotene, provitamin A activity, dehydroascorbic acid, L-ascorbic acid and total ascorbic acid content of ' 'jalapeho," 'bell," long green/red "chile," " serrano" and "yellow wax" peppers (Cupsicutn unnuum L.) at green and red stages of maturity were determined by HPLC. Effects of thermal processing on vitamin A and C retention in "jalapeno" peppers was also determined. Provitamin A activity ranged from 27.3 to 501.9 Retinol Equivalents (RE/loOg). Ascorbic acid concentration ranged from 76.1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
120
3
12

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(165 citation statements)
references
References 10 publications
22
120
3
12
Order By: Relevance
“…Josefa et al (2006) reported that the ascorbic acid content in sweet pepper was dependent on the fruit maturity state. Some authors have found divergences in ascorbic acid content of 30% between red and green peppers (Howard et al, 1994). Our results agreed with these findings, and 45 DFS contained more ascorbic acid.…”
Section: Ascorbic Acid Contentsupporting
confidence: 83%
“…Josefa et al (2006) reported that the ascorbic acid content in sweet pepper was dependent on the fruit maturity state. Some authors have found divergences in ascorbic acid content of 30% between red and green peppers (Howard et al, 1994). Our results agreed with these findings, and 45 DFS contained more ascorbic acid.…”
Section: Ascorbic Acid Contentsupporting
confidence: 83%
“…Total vitamin C of red pepper was about 30% higher than that of green pepper (Howard et al, 1994). Tomato fruit harvested green and ripened at 20°C to table-ripeness contained less AA than those harvested at the tableripe stage .…”
Section: Maturity At Har6estmentioning
confidence: 89%
“…The colour of capsicum fruit is due to the presence of lycopene, xanthophylls and carotene, the latter being dominant in yellow types (Norman 1992). Peppers consumption provides vitamin A and C and antioxidant activity in the diet (Howard et al 1994). Majority of the peppers cultivated in Nigeria are used in stews and local dishes.…”
Section: Introductionmentioning
confidence: 99%